2019
DOI: 10.1186/s12870-019-1681-6
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide investigation of the AP2/ERF gene family in tartary buckwheat (Fagopyum Tataricum)

Abstract: Background AP2/ERF transcription factors perform indispensable functions in various biological processes, such as plant growth, development, biotic and abiotic stresses responses. The AP2/ERF transcription factor family has been identified in many plants, and several AP2/ERF transcription factors from Arabidopsis thaliana ( A. thaliana ) have been functionally characterized. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 62 publications
19
58
0
Order By: Relevance
“…The motif analysis of the DlAP2/ERF superfamily showed that most of the AP2/ERF superfamily members contained motif-1, motif-2, motif-3, and motif-4 related to the AP2 domain. This result is similar to what was found in tartary buckwheat [37]. Motif-6 and motif-10 were detected specifically in the AP2 family, indicating that they may play a unique role in the AP2 family.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The motif analysis of the DlAP2/ERF superfamily showed that most of the AP2/ERF superfamily members contained motif-1, motif-2, motif-3, and motif-4 related to the AP2 domain. This result is similar to what was found in tartary buckwheat [37]. Motif-6 and motif-10 were detected specifically in the AP2 family, indicating that they may play a unique role in the AP2 family.…”
Section: Discussionsupporting
confidence: 88%
“…Although some motifs of the AP2/ERF superfamily were highly conserved, the unique motifs in different groups may have important functions in longan; however, these functions require further investigation. Structural analysis of the AP2/ERF superfamily showed that 82% of the DlERF and all of the DlRAV genes had no intron, whereas the AP2 family and Soloist genes had from one to nine introns, which is similar to what was found for AP2/ERF genes in tartary buckwheat [37]. The differences between the structures of ERF, RAV, and AP2 family genes indicated that they had largely differentiated during the evolution of the longan genome, and thus may have great functional differentiation.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Previous studies found that intron number and distribution are related to plant evolution, and introns of the ERF family genes were probably lost during evolution in higher plants [27,28]. In total, 215 of the 301 members (70%) of the ERF family had no introns, which was a little less than that of tartary buckwheat [24] and also consistent with previous findings.…”
Section: Discussionsupporting
confidence: 90%
“…S1). For example, the WLG element (58th-60th amino acids; 58-60AA) was highly conserved in in the ERF and RAV families; alternatively, in the AP2 family, the conserved sequences from 58-60AA were converted into YLG elements [24]. In many species, these conserved amino acid profiles contribute to convincing classification of AP2/ERF genes.…”
Section: Resultsmentioning
confidence: 99%